1993
DOI: 10.1073/pnas.90.10.4616
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian eukaryotic initiation factor 2 alpha kinases functionally substitute for GCN2 protein kinase in the GCN4 translational control mechanism of yeast.

Abstract: Phosphorylation of the a subunit of eukaryotic initiation factor 2 (eIF-2a) in Saccharomyces cerevisiae by the GCN2 protein kinase stimulates the translation of GCN4 mRNA. The protein kinases heme-regulated inhibitor of translation (HRI) and double-stranded RNA-dependent eIF-2a protein kinase (dsRNA-PK) inhibit initiation of translation in mammalian cells by phosphorylating Ser-51 of eIF-2a. We show that HRI and dsRNA-PK phosphorylate yeast eIF-2a in vitro and in vivo and functionally substitute for GCN2 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
167
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(186 citation statements)
references
References 16 publications
(26 reference statements)
15
167
0
Order By: Relevance
“…These results support the idea that GADD34 recruits PP1 to dephosphorylate eIF2α without affecting GCN2 kinase activity. Previously, it was shown that overexpression of human PKR is lethal in yeast because of the high levels of eIF2α phosphorylation and inhibition of translation (27,28). To test whether expression of GADD34 would suppress the toxicity associated with high-level expression of PKR in yeast, vectors encoding different variants of GADD34 were introduced into a yeast strain containing one copy of the human PKR gene.…”
Section: Gadd34 Promotesmentioning
confidence: 99%
“…These results support the idea that GADD34 recruits PP1 to dephosphorylate eIF2α without affecting GCN2 kinase activity. Previously, it was shown that overexpression of human PKR is lethal in yeast because of the high levels of eIF2α phosphorylation and inhibition of translation (27,28). To test whether expression of GADD34 would suppress the toxicity associated with high-level expression of PKR in yeast, vectors encoding different variants of GADD34 were introduced into a yeast strain containing one copy of the human PKR gene.…”
Section: Gadd34 Promotesmentioning
confidence: 99%
“…Because PERK is a member of the eIF2␣ kinase family, we considered it likely that another family member might cooperate and thereby promote eIF2␣ phosphorylation and attenuation of cyclin D1 synthesis (Dever et al, 1993). Two candidates for a redundant eIF2␣ kinase include PKR and GCN2, which are activated by double-stranded RNA and nutrient deprivation, respectively.…”
Section: Cyclin D1 Loss Requires Phosphorylation Of Eif2␣mentioning
confidence: 99%
“…Indeed, cyclin D1 protein levels were maintained in eIF2␣ S51A knockin fibroblasts after ER stress, demonstrating that cyclin D1 loss was absolutely dependent upon eIF2␣ phosphorylation. Furthermore, eIF2␣ S51A fibroblasts failed to arrest in G 1 phase during ER stress, providing further support for the requirement for eIF2␣ phosphorylation in cyclin D1 regulation.Because PERK is a member of the eIF2␣ kinase family, we considered it likely that another family member might cooperate and thereby promote eIF2␣ phosphorylation and attenuation of cyclin D1 synthesis (Dever et al, 1993). Two candidates for a redundant eIF2␣ kinase include PKR and GCN2, which are activated by double-stranded RNA and nutrient deprivation, respectively.…”
mentioning
confidence: 99%
“…High-level expression of human PKR is toxic in yeast because of phosphorylation of eIF2␣ and the attendant inhibition of translation initiation (13,14). Substitution of Ser-51 in eIF2␣ by Ala suppresses PKR toxicity as do mutations that block kinase activity (9,14,15).…”
mentioning
confidence: 99%